Multiresolution Transforms in Modern Image and Video Coding Systems - Malvar, Henrique S. (Independent Component Analyses, Wavelets, Unsupervised Smart Sensors, and Neural Networks II, 2004)
This paper presents a brief overview of the multiresolution transform designs used in a few image and video compression systems, namely H.264, PTC (progressive transform coder), and JPEG2000. The first two use hierarchical transforms, and the third uses wavelet transforms. We review the basis constructions for the hierarchical transforms, and compare some of their characteristics with those of wavelet transforms. In terms of compression performance as measured by peak-signal to noise ratio, H.264 provides the best performance, but at much higher computational complexity. In terms of visual quality, the multiresolution transforms provide an improvement over block (single resolution) transforms.